Inhibitory role of oxytocin in psychostimulant-induced psychological dependence and its effects on dopaminergic and glutaminergic transmission - Yang Jing-yu; Qi Jia; Han Wen-yan; Wang Fang; Wu Chun-fu (Acta Pharmacologica Sinica, 2016)
Psychostimulants are frequently abused as a result of their stimulatory effects on several neurotransmitter systems within the central nervous system. Both dopaminergic and glutaminergic neurotransmissions have been closely associated with psychostimulant dependence. In addition to its classical endocrine function in the periphery, oxytocin, an important neurohypophyseal neuropeptide in the central nervous system, has a wide range of behavioral effects, including regulating drug abuse. The present paper reviews the progress of research into the role of oxytocin in reducing psychostimulant-induced psychological dependence and the mechanisms by which oxytocin mediates its effects.